Perceptions about the secular State in a confessional State (Revista Rupturas, 2022)
This article exposes the socio-legal path of Costa Rica towards its last threshold of secularization (Baubérot 2007), accompanied by the explanatory distinction of the constitutional reforms and the respective proposals for constitutional reform, linked to the confessional and secular nature of the State. Subsequently, the cultural transformations in public opinion are examined, in terms of perceptions and expectations (Friedman 2011), about the management of religion by the State, based on specialized surveys on beliefs and values carried out by the National University (Costa Rica) in 2013 and 2018, which make it possible to measure the changes in process within the imagined community (Anderson 2002) and community to imagine.
Keywords: laicity; confessionalism; Costa Rica; religion; political constitution